The Development Study of the Drag Coefficient of Solid Cylinder on Inclined Plane in Water - Ariefka, Reza; Pramudya, Yudhiakto (Trends in Sciences, 2022)
The dynamic resistance of a fluid to a cylinder rolling on an inclined plane in water has been experimentally studied. This creates problems in the form of solid-liquid interactions, which include landslides on the seabed and debris flows on the seabed that cause Tsunamis. The development of flow around a rolling cylinder is described to highlight the implications on the nature of the hydrodynamic force coefficient acting on the cylinder as resistance. The coefficient of drag on the cylinder when rolling on an inclined plane in water is the coefficient of drag that prevents the cylinder from rolling. In addition, other external force coefficients (besides the drag coefficient) also impede the cylinder motion. The equation of motion of the cylinder is solved with experimental data which is used as the most suitable solution to get the drag coefficient value. The movement of the cylinder is also not perfectly linear because there is a force from the side of the track and the cylinder moves slightly zigzag in 1-D motion. HIGHLIGHTS In this study, we present the experimental results of cylindrical drag coefficients of various materials on inclined planes in water as modeling of broader scientific problems, especially the potential for hydrometeorological and sedimentation disasters Fluid dynamics of the cylinder drag force on an inclined plane in water were measured experimentally The motion of the cylinder on an inclined plane in water is recorded, then the recorded video is processed using Logger Pro to obtain experimental time, speed, and position data which is processed using the appropriate mathematical equations GRAPHICAL ABSTRACT